A mixed integer linear programming model for designing a green closed-loop supply chain network considering location-routing problem. Issue 2 (20th May 2020) - Sadeghi, Alvand; Mina, Hassan; Bahrami, Niloofar
In today's business environment, reusing the products could result in a great deal of supply chains cost reductions. Additionally, environmental regulations and customers' increasing expectations leave companies no choice but applying the return policy. In this regard, designing a supply chain network incorporating the reverse flow can provide environmental requirements in addition to economic objectives. In this paper, a new mixed integer linear programming (MILP) model is developed for a closed-loop supply chain network (CLSCN) design. The proposed model is multi-period and multi-product that covers facility location and routing of heterogeneous vehicle fleets, simultaneously. The efficiency of the model is validated based on a real case in production and distribution chain of automotive spare parts manufacturing company in Iran. Managerial insights are gained through the numerical results.